Isolasi Dan Karakterisasi Bakteri Selulolitik Biopori Sebagai Upaya Awal Percepatan Proses Pengomposan - Wardha Maulidya Pratiwi; Rana Yumna Nabila; Heliza Amalini; Guntur Trimulyono (Biotropic : The Journal of Tropical Biology, 2020)
The purpose of this study was to obtain cellulolytic bacterial isolates isolated from leaf litter in absorption holes biopori FMIPA Unesa and obtain the most optimal cellulolytic bacterial isolates in cellulose degradation. This research was an observational study and the data were analyzed descriptively. Stages of the study began with bacterial isolation, cellulolytic ability testing, and characterization of cellulolytic bacterial isolates. Bacterial isolation was carried out by the pour plate method, isolation was carried out by the streak plate method, cellulolytic testing was carried out using Carboxy Methyl Cellulose media which was given Congo red 1%. While the isolation characterization was done morphologically, physiologically, and biochemically. The results obtained 15 isolates of cellulolytic bacteria that were tested for their ability to degrade cellulose. Cellulolytic test results showed that 6 isolates, namely BS1, BS7, BS10, BS11, BS14, and BS15 had a cellulolytic index of 0.8, 0.8, 0.8, 0.8, 0.8, 0.8. and 1. Isolates BS15 is the most optimal isolate in cellulose degradation with characteristics of the punctiform colony, yellow pigmentation, entire edge, convex elevation, optical opaque and smooth surface, produces catalase enzymes, is non-motile and can ferment in glucose and starch but cannot ferment lactose and also a Gram-negative